SUPERVISI AKADEMIK MEMODERASI PENGARUH MOTIVASI DAN KEPUASAN KERJA TERHADAP KINERJA GURU (Studi pada guru SMP Negeri di sub rayon 07 kota Semarang) - Hetty, Cey (Students Journal of Economic and Management, 2012)
This study aims to examine the influence of work motivation, work satisfaction and academic supervision to teacher performance. The specific objectives of this study are to examine the role of academic supervision moderating influence ofÂ work motivation and work satisfaction to teacher performance. The usefulness of the study is to clarify and extend previous study on the role of academic supervision moderating influence of work motivation and work satisfaction to teacher performance. This study used an accidental sampling of state junior high school teachers at sub rayon 07 Semarang City as much as 138 teachers. This study used a single period in 2012. This study examined the relations between interaction of academic supervision and work motivation to teacher performance and interaction of academic supervision and work satisfaction to teacher performance. The method used multiple regression analyses based on moderating model. The results show that: (1) work motivation has positive and significant impact to teacher performance, (2) work satisfactionÂ has positive and significant impact to teacher performance, (3) academic supervision has positive impact but not significant to teacher performance,(4) academic supervision doesnât moderate the influence of work motivation to teacher performance, (5) academic supervision doesnât moderate the influence of work satisfaction to teacher performance. Key words: work motivation, work satisfaction, academic supervision, andteacher performance